Representation of Human Rights Violation in The Novels by Leila S. Chudori - Apriyani, Tristanti; Lixian, Xiao; Daulay, Resneri (BAHASTRA, 2025)
Many authors use the theme of human rights in literature to highlight and address social issues. Similarly, Leila S. Chudori explores human rights violations in her novels Pulang (2012), Laut Bercerita (2017), and Namaku Alam (2023). This study analyzes the depiction of human rights abuses in these works as reflections of social realities during Indonesia's New Order era, employing new historicism theory. Using a qualitative descriptive approach, data were collected through reading, recording, and literature review. To ensure validity, semantic checks were applied, while reliability was confirmed through intrarater and interrater methods. Data analysis combined archaeological method and thick description techniques. The findings reveal that Chudori's novels effectively depict various human rights violations experienced during the New Order period,  such as political imprisonment, enforced disappearances, censorship, or state violence to give readers a clearer understanding of the study's scope offering critical insight into the era's social and political context. This study contributes by illuminating how Indonesian literary narratives reinterpret New Order history, thereby bridging historical memory dan cultural expression.